The Effect of Chamomile Extract on Coronavirus - Mohaddeseh Sadat Moghaddam; Niyusha Torabzadeh Khorasani; Reza Assaran Darban; Hamid reza Rahimi (Reviews in Clinical Medicine, 2021)
Acute respiratory Syndrome (SARS) is an uncommon respiratory illness that is transmitted primarily by respiratory droplets or direct contact with an infected person. The COVID-19 initially appeared in late 2019 in Wuhan, China, and spread everywhere around the globe. Earlier in 2003, the coronavirus was known due to the human SARS-CoV virus, which infected 8,000 people and caused 800 deaths in southeast Asia and Canada. It should be mentioned that in 2012, another coronavirus, called Middle East respiratory syndrome coronavirus, infected Saudi Arabia and 27 other countries. The SARS-CoV2 belongs to a family of viruses called Coronaviruses that can infect bats, birds, pigs, cows, and different mammals. Some plant extracts are shown to inhibit microorganism replication and may be utilized in medication to treat infectious and non-infectious diseases, one of which is chamomile. chamomile medicinal plant, that has 120 biologically active compounds, the most necessary of which are flavonoids, like apigenin and luteolin, that are shown to possess antiviral activity.